Professional C++ - Gregoire, Marc; Solter, Nicholas 1977-; Kleper, Scott 1977- (John Wiley & Sons, 2011)
Essential reading for experienced developers who are determined to master the latest release of C++Although C++ is often the language of choice from game programming to major commercial software applications, it is also one of the most difficult to master. With this no-nonsense book, you will learn to conquer the latest release of C++. The author deciphers little-known features of C++, shares detailed code examples that you can then plug into your own code, and reveals the significant changes to C++ that accompany the latest release. You'll discover how to design and build applications that so.
Handling Copying and Assignment. - Includes bibliographical references and index. - Print version record
Keywords: C++ (Computer program language); C++ (Langage de programmation); COMPUTERS; Programming Languages; C♯; COMPUTERS; Programming Languages; Java; COMPUTERS; Programming Languages; Pascal; Computers and IT; dissertations; Academic theses; Thèses et écrits académiques